ISBAT NIKAH SEBAGAI MEKANISME LEGALISASI NIKAH SIRI (ANALISIS KRITIS TERHADAP KEPASTIAN HUKUM DAN PERLINDUNGAN PEREMPUAN) - Novita Rahim (Proceeding International Conference on Social Sciences, 2026)
This study aims to critically analyze the legal construction of Marriage Confirmation in the dialectic between the enforcement of the principle of legal certainty and the demands for the protection of women's and children's rights. The research method used is normative-juridical with a conceptual and legislative approach, and links the findings with Gustav Radbruch's Theory of Legal Purpose and Lawrence M. Friedman's Theory of Legal Systems. The results of the study indicate that Marriage Confirmation functions as a noble reactionary mechanism to guarantee substantive justice, but paradoxically becomes a loophole for legalization (legal smuggling) for unregistered marriages, which fundamentally damages the legal culture of society and weakens the substance of law (Law No. 1/1974). Furthermore, the disparity in decisions between Religious Courts, especially in accepting Marriage Confirmation after 1974, undermines the principle of legal certainty and, based on Feminist Legal Theory, places women's protection in an arbitrary position. It is concluded that protection efforts through Marriage Confirmation should not sacrifice legal integrity. It is recommended that the Supreme Court immediately issue a uniform SEMA to harmonize decisions and revise Article 7 of the KHI to limit discretion to truly urgent cases (ius necessitatis).